Assessing the Role of Mobile Libraries in Enhancing Literacy in Underserved Communities - Kalai Lakshmi, T. R.; Nanda, Susama; Choudhary, Varsha; Prabhu, Sushmitha; Tuteja, Gaurav; Biswal, Saroj Kanta (Indian Journal of Information Sources and Services, 2025)
Purpose: Mobile libraries serve as an innovative intervention by delivering educational materials and literacy programs directly populations with restricted access to formal learning institutions. Agricultural informationalization, which integrates digital and mobile solutions to support rural economic growth, exemplifies how mobile knowledge systems can be structured to enhance educational outreach. Mobile libraries improve reading habits, functional literacy, and lifelong learning by leveraging flexible service models, and assessing effectiveness underserved communities through accessibility, engagement, and educational outcomes. Methodology: Data were collected from 487 participants, including mobile library users, educators, facilitators, and local administrators, using structured surveys and literacy assessment tools. The investigation used stratified sampling to ensure diverse representation across age groups and literacy levels, and quantitative statistical models’ multiple regression and ANOVA examine relationships between mobile library management usage and literacy improvement. The IBM SPSS software version 27.0 utilized for data analysis, evaluating variables reading frequency, comprehension levels, resource accessibility, user engagement, utilizing mobile library deployment strategies and digital integration. Results: Results indicate statistically significant correlation between mobile library access and literacy improvement, with effects on reading comprehension and functional literacy skills. The multiple regression analysis revealed that mobile library usage has strongest impact on literacy improvement (???? = ????.????????????,???? < ????.????????????), explaining 46.4% of the variance. Participants showed significant literacy gains, with reading comprehension increasing by 3.3 points (???? = ????????.????????,???? < ????.????????????). Conclusion: The findings highlight the role of mobile libraries in mitigating educational disparities, reinforcing their potential as scalable solutions for literacy development in underserved regions.